Effectiveness of the Promising Neighbourhoods community program in 0-to 12-year-olds: A difference-in-difference analysis - Mirte Boelens; Hein Raat; Harrie Jonkman; Clemens M.H. Hosman; Denis Wiering; Wilma Jansen (Elsevier, 2022)
Objective: The purpose of this study was to evaluate a collaborative community-based program that aims to a) increase the health, safety and talent development of youth, and b) contribute to the reduction of socioeconomic inequalities. Methods: A difference-in difference design with two separate cross-sectional samples in 2018 (n = 984) and 2021 (n = 413) among 0- to 12-year-olds with an intervention and comparator condition was used. The program, called Promising Neighbourhoods, consists of collaboration with community stakeholders, data-based priority setting, knowledge-and theory-based policies, and evidence-based interventions. The program was implemented in three neighbourhoods which were compared with three similar comparator neighbourhoods in which the program was not implemented. Logistic difference-in-difference regression was used to test effectiveness of the intervention on informal parenting support, outdoor-play, sport club membership, general health and risk of emotional and behavioural difficulties and to examine differences in intervention effects between children with a lower or higher socioeconomic status. Results: A significant intervention effect of the Promising Neighbourhoods program after two-years was found for outdoor-play (OR 0.61; 95%CI 0.37, 0.99). No other significant intervention effects were found for other outcomes. No different interventions effects were found for children with a lower or higher socioeconomic status on outcomes. Conclusion: The findings of this study indicate a positive intervention effect for one of the outcomes in 0- to 12-year-olds. Further mixed-methods evaluation research and using longer follow-up periods are needed to examine the value of these type of programs. Further development of Promising Neighbourhoods seems warranted. Trial registration: This study was prospectively registered in the Netherlands National Trial Register (Number: NL7279) on 26 September 2018.